Living labs to accelerate innovation - Keyson, D.; Morrison, Greg; Baedeker, C.; Liedtke, C. (2016)
© Springer International Publishing Switzerland 2017.A key goal of LivingLabs is to provide industry, including large companies and SMEs, knowledge institutes and policymakers with a unique new infrastructure in testing and the co-development of sustainable products, services, legislation and combinations of these, takes place directly with users. The three- Tier Model of living lab research which aims to connect industry, academic, and public stakeholders, while facilitating user-centred studies, is presented in this section consisting of: (a) insight research involving the study of current practices in existing homes, (b) studies in prototype houses equipped with innovative products and services focused on sustainable living, and (c) field testing, in which research prototypes are up-scaled such that existing homes can be equipped with innovative sustainable technologies.